(untitled) (Swiss Medical Weekly, 2001)
Objective: To review the diagnostic experience with acute haematogenous osteomyelitis (AHOM) and/or septic arthritis at our institution. Methods: Retrospective review of the medical records of those patients with a bacteriologically and/or radiologically confirmed diagnosis, hospitalised in the University Children’s Hospital Basel, Switzerland between January 1980 and July 2000. Results: 90 patients (61% males), 4 weeks to 14 years of age, met the inclusion criteria. Median duration of disease prior to hospitalisation was 3 days (range 0-14); 88% were admitted during the first week after onset of complaints. 81 patients received no antimicrobial therapy prior to hospitalisation and are the subject of this presentation. ESR (1st hour in mm; median 36; range 11-124), CRP (mg/l; median 64; range 0-221) and WBC (x 10(9)/l; median 13; range 5-34) were elevated in 100%, 82% and 58% of patients, respectively. Blood cultures (BC) and/or tissue cultures (TC) were performed in 79 (98%) patients. Overall, bacteria were isolated from 53 patients (65%) with Staph. aureus as the most frequent organism (n = 31; 50%). BC were performed in 67 patients and yielded 35 (52%) positive cultures; TC (n = 47) yielded 27 (57%) isolates. In 34 patients with both BC and TC performed, only 12 (35%) were positive in both tests. Diagnostic findings were observed in 23 (59%) of 39 plain radiographs, 31 (56%) of 55 sonograms, 39 (89%) of 44 99mTc-labeled bone scans and 4 (100%) of 4 MRI. 41 patients with diagnostic radiological findings had consecutive TC yielding 30 (73%) bacteriological isolates. Median duration of hospitalisation was 15 days (range 2-66). Conclusion: Our data indicate that the diagnostic procedures of choice should be 1) early bone scan or MRI, 2) BC and 3) TC. Of supportive laboratory parameters, ESR and CRP were most valuable in our hands.